Case Report pada Ny.K Multipara dengan Postpartum Blues Masalah Laktasi - Sanjung Alam Amanda; Rahayu Sumaningsih; Agung Suharto; Sulikah . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Lactation problems in mothers with postpartum blues may occur due to psychological changes affecting oxytocin and prolactin, resulting in inadequate breast milk production and ejection. This article aimed to describe comprehensive midwifery care for Mrs. K, a multiparous mother with postpartum blues accompanied by lactation problems. This case report used SOAP documentation. The assessment showed that the mother experienced frequent crying, anxiety, lack of confidence in caring for her baby, and inadequate breast milk production. The interventions included education about postpartum blues, proper breastfeeding and attachment techniques, on-demand breastfeeding, breast care, adequate nutrition and rest, and support from the husband and family. The evaluation showed an improvement in the mother’s psychological condition, reduced anxiety, increased breast milk production, and more effective breastfeeding. Comprehensive midwifery care can help reduce postpartum blues symptoms and support successful lactation.